"I've Always Been Scared That Someday I'm Going to Sell Out": Exploring the relationship between Political Identity and Learning in Computer Science Education. Issue 2 (2nd April 2020) - Vakil, Sepehr
Abstract: While academic, cultural, and racial identities have been important concepts in sociocultural theories of learning and development, less attention has been given to political identity. Research on political identities in education tends to be limited to critical pedagogy or civic education contexts, leaving unexamined the role of political identity in supposedly neutral settings, like a computer science (CS) classroom. In this study I offer a conceptual framework that draws on theories of political identity and sociocultural theories of learning to illuminate a process I call disciplinary values interpretation —a process by which students reflect on the values of a disciplinary domain, as well as who they are and might become in relation to the domain. I then operationalize the framework by analyzing the ways in which students' political identities interacted with their learning processes in a social design experiment conducted in collaboration with a high school teacher in a Computer Science and Technology academy of a large urban high school. Through case studies of two 10th grade students, Stacey and Lupe, I argue that the opportunity to design socially relevant technology provided new resources for disciplinary values interpretation, and had significant implications for how students came to view their own political identities and futures within the discipline of CS. This research has implications for ethical/political theories of learning and also contributes to enduring questions about identification and inequality in education.